On a p -Laplacian system with critical Hardy - Sobolev exponents and critical Sobolev exponents - Nyamoradi, N. (Ukrains’kyi Matematychnyi Zhurnal, 2012)
We consider a quasilinear elliptic system involving the critical Hardy - Sobolev exponent and Sobolev exponent. Using variational methods and analytic techniques, we establish the existence of positive solutions of the system.